Transition metal(II) complexes featuring push-pull dianionic Schiff base ligands: synthesis, crystal structure, electrochemical, and NLO studies. Issue 20 (6th October 2020) - Celedon, Salvador; Roisnel, Thierry; Carrillo, David; Ledoux-Rak, Isabelle; Hamon, Jean-Rene; Manzur, Carolina
Abstract: The present study reports the synthesis and characterization of a family of three new neutral Zn(II), Cu(II), Co(II) bimetallic (2–4 ), and one ionic Co(II) trimetallic (5 ) complexes of ferrocene-containing unsymmetrically-substituted N2 O2 tetradentate Schiff base ligands. They were all prepared via a three-component one-pot template reaction involving the 4-hydroxyphenyl substituted ferrocenyl-containing half unit Fc-C(=O)CH = C(4-C6 H4 OH)NH-CH2 CH2 NH2 (Fc = ferrocenyl = (η 5 -C5 H5 )Fe(η 5 -C5 H4 )), metal(II) acetate, and 5-nitrosalicylaldehyde (for 2–4 ) or the organometallic salicylaldehyde [Cp*Ru(η 6 -2-OH-C6 H4 CHO)]PF6 (for 5 ) (Cp* = η 5 -C5 Me5 ). The four complexes were isolated as air and moisture insensitive solids in yields > 80%. They were characterized using several analytical techniques such as CHN analyses, ESI mass, FT-IR, UV-vis, and NMR spectroscopy, including single crystal X-ray diffraction analysis. The crystal structure of 3 reveals that the four-coordinate copper ion adopts a square planar geometry with two nitrogen and two oxygen atoms as donors occupying cis positions. An electrochemical study utilizing cyclic voltammetry showed for each compound a reversible redox process ascribed to the Fe(II)/Fe(III) couple of the appended donor ferrocene. The largest anodic potentials were measured for the two Co(II) species. The second-order NLO responses of the push-pull chromophores 2–5 have been determined by harmonic light scattering measurements in N, N-dimethylformamide solutions at 1.91 μm incident wavelength, and rather high, non-resonant quadratic hyperpolarizability β values ranging from 140 to 280 × 10 −30  esu were determined. Graphical Abstract: